Instrumen Evaluasi Teks Berita Dalam Buku Teks BSE Bahasa Indonesia - Imam Safi'i; Ida Rufaidah; Uky Eji Anggara; Sobri Sobri (Universitas Mathla'ul Anwar Banten, 2021)
This article aims to describe the suitability of the newsprint evaluation instrument contained in the Indonesian Language BSE textbook with the 2013 Curriculum competency standards. This type of research is a qualitative research. The research method used is content analysis, namely by combining the appropriateness of the contents of the evaluation instrument with the basic competencies in the 2013 Curriculum. The data sources of this research are a number of evaluation instruments about news text teaching materials contained in the BSE Indonesian language textbook for SMP class VIII. Based on the research that has been done, data obtained, that the level of conformity of the evaluation instrument with the basic competencies of the 2013 Curriculum related to news text teaching materials is 66%, while the discrepancy is 33%. The results of this study can be used as information to determine the quality of the evaluation instruments contained in Indonesian textbooks.